Crash patterns in two Chinese secondary cities, with comparisons to crash patterns in the United States. (25th November 2019) - Miller, Ted R.; Ringwalt, Christopher; Kaner, Emily; Paschall, Mallie J.; Grube, Joel W.
Abstract: Objective: Evaluations of drink-driving crash interventions and crash burden in middle-income countries often rely on assumptions supported by data from the United States. We described crashes using pooled survey data across 2 Chinese agricultural cities in the 600, 000 population range and then assessed comparability of selected crash characteristics to those in the United States. Methods: We conducted household interviews on drinking and related harms with representative samples of 1, 500 people aged 18 and over in both Jiangshan and Lanxi, China. Near the end of the survey, 2, 962 people responded to questions about motor vehicle crashes during the past year. We report survey data weighted to match the population demographically. Results: Across the 2 cities, 28% of adults were licensed drivers and 24% drove a motorized vehicle. Fifty-three respondents (unweighted) reported that they personally were involved in at least one crash in the past year. Among these, 32% (weighted) were driving a car, truck, or bus; 7.5% were driving a motorcycle; 9.5% were pedalcyclists; 17% were pedestrians; and 34% were passengers. Of the crashes, 42% involved just one motorized vehicle. Most crashes (62%) occurred in broad daylight, followed by at dawn or dusk (19%) and at night (19%). Only 4% were single-vehicle nighttime crashes. Someone was injured or killed in 22% of crashes. Respondents thought it likely that at least one driver was drinking alcohol in 21% of the crashes and thought it unlikely in 51%; the remaining 28% were unsure whether anyone was drinking or refused this question. Alcohol involvement was similar in injury and no-injury crashes. Respondents thought a driver had been drinking in 24% of daytime crashes, 34% of crashes at dawn or dusk, and 36% of nighttime crashes. All 3 crashes involving an alcohol-involved pedestrian or pedalcyclist also included an alcohol-involved driver. Respondents said that 40% of the crashes were reported to the police and 40% were not reported; the remaining 20% of respondents did not know whether anyone reported their crash. Among crashes where reporting status was known, all crashes with injuries were reported. Conclusions: Compared to published data, crash rates are similar among licensed drivers in the United States and these Chinese cities. The percentage of crashes that involved injury did not differ significantly between the 2 countries. Injury crashes were well reported in both. Crashes involving property damage only were significantly less likely to be reported to the police in the Chinese cities. Alcohol involvement rates in crashes were similar. Although our crash sample was small, some crash parameters appear to be transferable between these 2 countries.